The Effect of (Mostly Unskilled) Immigration on the Innovation of Italian Regions - Massimiliano Bratti; Chiara Conti (Institute for the Study of Labor (IZA), 2014)
We use small Italian regions (i.e. provinces) to investigate the causal effect of foreign immigration on innovation during 2003-2008. Using instrumental variables estimation (based on immigrants' enclaves), we find that the overall stock of immigrants did not have any effect on innovation. However, decomposing the overall effect into the contributions of low- and high-skilled migrants shows that an increase of 1 percentage point in the share of low-skilled migrants on the population reduces patent applications by about 0.2%. By contrast, the impact of high-skilled immigrants on innovation is positive, in line with the previous literature, but cannot be precisely estimated.
Keywords: O3; J2; 330; immigration; innovation; patent applications; regions; Italy